Surveillance, Whistleblowing or Ignorance of the GDPR? - Wasiak, Dariusz; Narolski, Jerzy; Soczyński, Tomasz (University of Wroclaw. Faculty of Law, Administration & Economics, 2021)
The article is an attempt to draw attention to the intention of the Ministry of Family and Social Policy to shape its own legal policy with regard to the ability of the officials of the Social Insurance Institution (ZUS) to obtain information about individuals subject to official control. Within the proposed changes to Art. 61a of the Act of 25 June 1999 on cash benefits from social insurance in the event of sickness and maternity (Journal of Laws 1999, 60.636, as amended), the Ministry, not taking into account the requirement to ensure the existence of constitutionally guaranteed rights and freedoms, consciously shapes the law positive for full-range surveillance of every person covered by the interest of ZUS. In such circumstances, after adopting the amendments by the Polish Parliament (Sejm), ZUS will be included in the group of law enforcement authorities, as the scope of powers and possibilities its officials in the field have of obtaining information will be unlimited.
Keywords: Ministry of Family and Social Policy; sickness benefit; surveillance; personal data; whistleblower; rights and freedoms; GDPR